The Implementation of Problem-Based Learning to Improve Mathematical Problem Solving Ability: A Case on Social Arithmetics - Laiya, Wirda S.; Abbas, Nurhayati; Nurwan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Mathematics plays a crucial role in fostering students’ logical, systematic, and critical thinking skills. However, many students still struggle to understand mathematical concepts that are closely related to real-life situations, such as social arithmetic. This study aims to improve students’ mathematical problem-solving skills through the implementation of the Problem-Based Learning (PBL) model. This research was conducted as Classroom Action Research (CAR) in class VII-1 of MTs. Negeri 1 Boalemo, involving 30 students. The study followed the Kemmis and McTaggart model, consisting of two cycles, each with four phases: planning, implementation, observation, and reflection. Data were collected using observation sheets to measure teacher and student activities, and problem-solving tests developed based on Polya’s indicators: understanding the problem, planning a solution, implementing the solution, and reviewing the result. The collected data were analyzed descriptively and quantitatively to determine the level of improvement. The results showed a significant increase in the learning process and student achievement. The teacher’s ability to manage learning increased from 55.56% in Cycle I to 88.89% in Cycle II. Student activity rose from 37.50% to 87.50%, and the number of students achieving mastery increased from 53.33% to 90%. Therefore, the PBL model effectively enhances students’ mathematical problem-solving abilities and promotes active, collaborative learning in the classroom.